2005
DOI: 10.1152/ajpendo.00031.2005
|View full text |Cite
|
Sign up to set email alerts
|

Zone-specific cell proliferation during adrenocortical regeneration after enucleation in rats

Abstract: A quantitative analysis of zone-specific proliferation was done to determine the recovery of adrenal cortical zonation during regeneration after enucleation. Adult male rats underwent adrenal enucleation [unilateral enucleation (ULE)] or sham surgery, both accompanied by contralateral adrenalectomy. At 2, 5, 10, and 28 days, blood and adrenals were collected to assess functional recovery. Adrenal sections were immunostained for Ki67 (proliferation), cytochrome P-450 aldosterone synthase (P-450aldo, glomerulosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…Nevertheless, mediation by the ANS appears not to be essential in the effects of Ex-4 on corticosterone circadian rhythm, since ULE rats receiving Ex-4 treatment also presented a disrupted corticosterone rhythm. It is known that adrenal enucleation impairs normal cortical function and that the adrenal cortex does not completely regenerate for approximately 4 weeks (14,71). However, previous studies have shown that rat cortical function, although not fully restored, is greatly recovered 7 days after adrenal enucleation and significant AM-PM differences in plasma corticosterone concentrations are found (71).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, mediation by the ANS appears not to be essential in the effects of Ex-4 on corticosterone circadian rhythm, since ULE rats receiving Ex-4 treatment also presented a disrupted corticosterone rhythm. It is known that adrenal enucleation impairs normal cortical function and that the adrenal cortex does not completely regenerate for approximately 4 weeks (14,71). However, previous studies have shown that rat cortical function, although not fully restored, is greatly recovered 7 days after adrenal enucleation and significant AM-PM differences in plasma corticosterone concentrations are found (71).…”
Section: Discussionmentioning
confidence: 97%
“…This study was developed to determine both the role of the adrenal medulla in Ex-4 effects on HPA axis and whether Ex-4 treatment could facilitate the recovery of normal steroidogenic function in a well-established model of adrenocortical regeneration, the unilateral enucleated (ULE) rat (14). Twelve animals underwent surgical enucleation of the left adrenal gland, while six were subjected to sham surgery of the left gland.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The rest of the glomerulosa is enigmatic, though because of its lack of significant steroidogenic function it has been postulated to be a stem cell population for both glomerulosa and fasciculata cells (Mitani et al 1996, Miyamoto et al 1999, 2001). Here, proof has been elusive, since mitoses can occur throughout the gland (Wright 1971, Horiba et al 1987, McNicol & Duffy 1987, Clark et al 1992, Basile & Holzwarth 1993, Holzwarth 1995, Zieleniewski et al 1995, McEwan et al 1996, Ennen et al 2005, including in the immediate subcapsular region and in the capsule itself (McNeill et al 2005). The possible function of the major, silent, part of the glomerulosa has been discussed elsewhere (Vinson 2003(Vinson , 2004, but taking this evidence at face value, the hypothesis emerges that the glomerulosa is probably not a stem cell population, but may be considered an essentially undifferentiated tissue on to which evolution has grafted some minimal (though crucial) steroidogenic function, in the form of CYP 11B2.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the accepted view is that the glomerulosa is the source of aldosterone secretion and the fasciculata and reticularis are the source of glucocorticoids (Deane 1962, Ogishima et al 1992, Vinson et al 1992, Ennen et al 2005 and (depending on species) androgens as well (Deane 1962, Parker et al 1983, Vinson et al 1992, Rehman & Carr 2004. Within this system, aldosterone secretion is under the regulation of angiotensin (and other agents) and adrenocorticotrophin (ACTH) supports fasciculata and reticularis functions.…”
Section: Introductionmentioning
confidence: 99%
“…For more than 60 years, it has been known that bilateral subcapsular enucleation of the adrenals in rodent models leads to the regeneration of adrenocortical mass within 4-6 weeks (47,48). Steroidogenic function can be detected as early as day-8 after enucleation, whereas full steroidogenic capacity continues developing for up to 6 weeks (47,49). A similar picture was also found when the adrenal cortical tissue with capsule attached was autotransplanted to a flank muscle pocket in a rodent model undergoing bilateral adrenalectomy (50).…”
Section: Adrenal Plasticitymentioning
confidence: 99%